PENGARUH PENERAPAN INOVASI RADIKAL DAN INKREMENTAL TERHADAP DAYA SAING USAHA PADA UMKM MAKANAN DAN MINUMAN DI KOTA CIREBON - Rusmanto, Sherly Putri Inggrianita; Prabowo, Fajar Sidiq Adi (Jurnal Wacana Ekonomi, 2025)
Dynamic business developments, especially in the MSME sector, encourage business actors to continue to create competitive advantages through innovation. This study aims to determine the effect of radical and incremental innovation on the competitiveness of food and beverage MSMEs in Cirebon City. The study used a quantitative descriptive method with data collection through online questionnaires to MSME actors, and analyzed using SEM through Smart PLS. The results of the study showed that both types of innovation have an effect on competitiveness, where radical innovation includes fundamental changes, while incremental innovation focuses on gradual improvements. Implementation of the right innovation strategy can strengthen the competitiveness of MSMEs in the midst of dynamic market competition. Keywords: MSME, Food and Beverage, Radical Innovation, Incremental Innovation, Business Competitiveness.